2018
DOI: 10.1371/journal.pone.0197345
|View full text |Cite
|
Sign up to set email alerts
|

UV/O3 treatment as a surface modification of rice husk towards preparation of novel biocomposites

Abstract: The use of rice husks (RH) to reinforce polymers in biocomposites are increasing tremendously. However, the incompatibility between the hydrophilic RH fibers and the hydrophobic thermoplastic matrices leads to unsatisfactory biocomposites. Surface modification of the fiber surface was carried out to improve the adhesion between fiber and matrix. In this study, the effect of surface modification of RH via alkali, acid and ultraviolet-ozonolysis (UV/O3) treatments on the properties of composites recycled high de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Several researchers evaluated the improved tensile strength properties between RH and the matrix resin using surface modification techniques such as esterification, silane treatment, fiber mercerization, or fiber surface modification. For example, Rajendran et al [ 25 ] treated RH with ultraviolet-ozonolysis and found that the treated RH composites improved the tensile strength by 5% compared to the composite with untreated RH. Bisht et al [ 26 ] used a mercerization treatment on RH flour and studied the effect on the tensile strength of RH/epoxy composites.…”
Section: Tensile Strength Of Rh Compositesmentioning
confidence: 99%
“…Several researchers evaluated the improved tensile strength properties between RH and the matrix resin using surface modification techniques such as esterification, silane treatment, fiber mercerization, or fiber surface modification. For example, Rajendran et al [ 25 ] treated RH with ultraviolet-ozonolysis and found that the treated RH composites improved the tensile strength by 5% compared to the composite with untreated RH. Bisht et al [ 26 ] used a mercerization treatment on RH flour and studied the effect on the tensile strength of RH/epoxy composites.…”
Section: Tensile Strength Of Rh Compositesmentioning
confidence: 99%
“…The main mechanism behind alkaline treatments is the removal of fibre constituents that prevents bonding with the polymer matrix, which include pectin, oils, lignin, wax and hemicellulose which is weaker than cellulose. After the removal of these constituents, it is observed that the surface of fibres is rougher and with some improvements to the mechanical properties of the composite as reported by Rajendran Royan et al [64]. However, the success and effectiveness of this treatment, depend on the concentration of the alkaline, treatment time, type of alkaline and temperature.…”
Section: Pre-processing Of Fibresmentioning
confidence: 78%
“…These processes can also reduce the hydroxyl groups and increase adhesion. In the case of UV/O3 treatments, there might also be an increase in active groups on the surface of the treated fibre, further promoting chemical bonding to the matrix [ 64 ].…”
Section: Processing Of Natural Fibres and Fabrication Of Filamentmentioning
confidence: 99%
See 1 more Smart Citation
“…The tensile strength of UV/O 3 -treated BCB showed about 5% increase. In addition, it reduced processing time and raw material wastage during BCB manufacturing [45]. This could facilitate the commercial production of sustainable and environmentally friendly materials.…”
Section: Introductionmentioning
confidence: 99%